Daily Consumption of an Anthocyanin-Rich Extract Made From New Zealand Blackcurrants for 5 Weeks Supports Exercise Recovery Through the Management of Oxidative Stress and Inflammation: A Randomized Placebo Controlled Pilot Study - Hurst, Roger D.; Lyall, Kirsty A.; Wells, Robyn W.; Sawyer, Gregory M.; Lomiwes, Dominic; Ngametua, Nayer; Hurst, Suzanne M. (Frontiers in Nutrition, 2020)
Background: Regular exercise is essential to a healthy lifestyle but evokes an oxidative and inflammatory stress. Depending upon its intensity and duration this can result in either beneficial adaptive changes or underlying tissue damage that impacts upon long-term health and individual sporting training schedules. Functional foods containing plant bioactives have potential to support exercise through management of the detrimental aspects of exercise and complement ergonomic adaptive benefits. Aim: Previously we reported that a single consumption of a 3.2 mg/kg New Zealand blackcurrant anthocyanin-rich extract (BAE) 1 hr before a 30 min rowing exercise attenuated moderate exercise-mediated oxidative stress and supported innate immunity. Here we evaluate whether the efficacy of a single consumption of BAE consumed 1 hr prior to exercise is changedendures after extended daily BAE consumption for 5 weeks. Results: On week 1, a single consumption of BAE 1 hr before a 30 min row mediated a significant (p<0.05) 46% reduction in post-exercise-induced malondialdehyde (MDA) by 2 hr compared to a 30% reduction in the placebo group. Similar efficacy was observed 5 weeks later after daily consumption of BAE. In addition, daily BAE consumption for 5 weeks improved the efficacy to (a) reduce post-exercise plasma reactive oxygen species (ROS)-generating ability, (ab) resolve acute inflammation, and (bc) increased plasma IL-10, salivary beta-defensin 2 (BD2) and secretory IgA. Although no change in plasma antioxidant capacity was detected, a significant (p<0.009) positive correlation between plasma IL-10 and plasma antioxidant capacity (R2=0.35) was observed on week 6 after 5-week BAE consumption suggesting IL-10 influences antioxidant properties. Using a differentiated myotubule cell-line revealed that whilst IL-10 had no direct antioxidant neutralizing action, longer-term exposure (24 hr) attenuated 2,2'-Azobis(2-amidinopropane) dihydrochloride (AAPH)-induced myotubule oxidative stress, supporting a putative role for IL-10 in the modulation of cellular antioxidant systems. Conclusions: Daily consumption of BAE for 5 weeks does not lead to a loss of efficacy due to nutritional tolerance. Indeed daily consumption of BAE for 5 weeks serves to enhance the exercise recovery effectiveness of a singlen acute consumption of BAE and promotes beneficial / protective antioxidant / anti-inflammatory cellular events that facilitate exercise recovery.